The role of smallholder farmers in seed-production systems - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Summary report and recommendations of a CTA study visit, Zimbabwe. 1999. (see Spore 86, p. 11)CTA, 2000. 33pp.ISBN 92 9081 2222CTA number 986. 5 credit points